Vehicular networks for reduction of fuel consumption and CO2 emission - Alsabaan, M; Naik, K; Khalifa, T; Nayak, A (2010 8th IEEE International Conference on Industrial Informatics, 2010)
With recent advances in the development of wireless communication networks, vehicular networks have been receiving considerable research interest. One of the major applications of vehicular networks is Intelligent Transportation Systems (ITS). To exchange and distribute messages, geocast routing protocols have been proposed for ITS applications. Almost all of these protocols evaluate network-centric performance measures, instead of evaluating the impact of the protocol on the vehicular system. Nowadays, rising fuel costs and the harmful effects of air pollutants have been the subject of considerable public debate. Therefore, it is desirable to create new economical and environmentally friendly geocast (EEFG) protocols, which focus on minimizing vehicle fuel consumption and emissions. The main goals of this paper are to motivate communications researchers to design EEFG protocols, demonstrate the ability to integrate fuel and emission models with vehicular networks, and illustrate the benefit of transmitting the traffic light signal information to vehicles for fuel consumption and emission reduction. By means of an example, we show how vehicular networks can be used to reduce fuel consumption and carbon dioxide (CO 2 ) emission in a city environment. Simulation results demonstrate that vehicle fuel consumption and CO 2 emission will be reduced if such an EEFG protocol is used.